Patrol Music Festival For Increasing Solidarity Of Santri In Kropoh Village (Kompersa) Ra'as District, Sumenep, Madura - Ismail, Nur Mahmudi; Amaluddin, M. Rizki (LP2M UIN KH.Achmad Siddiq Jember, 2023)
Patrol music (Tok-tok) was originally a musical accompaniment used to accompany night patrols in villages and townships and mark the hour or when there was danger. However, gradually, this practice began to be abandoned in some areas because there were not many night patrols. Patrol Music (Tok-tok) is a form of cultural activity usually contested when the holy month of Ramadan arrives. Playing patrol music takes a group of people with various equipment who generally use traditional musical instruments such as kentongan. It is not uncommon in practice for musicians or music patrol players to use household items such as pots, frying pans, used bottles, spoons, and so on. The Santri Unity Communication (KOMPERSA) is an inter-student organization from Kropoh Village, Ra'as District, Sumenep Regency. Islamic boarding schools, Java and Madura, unite students through several activities, such as the Patrol Music Festival. The purpose of this study was to increase solidarity between Islamic boarding school students who are in the horseshoe area and Madura who come from Kropoh Village, Ra'as District, Sumenep Regency, during the Islamic boarding school holidays, especially during the holy month of Ramadan through the Patrol music festival. This research uses a descriptive qualitative method. The results of this study indicate that Patrol Music (Tok-tok) has an excellent impact on the communication of the santri unity (KOMPERSA). The solidarity built between the students had a significant influence when the festival was held, such as building harmonious communication between fellow students, even though they lived differently in the pesantren environment, both in the Horseshoe area and the Madura area. They need each other because there are similarities as someone with a santri identity who must apply the knowledge gained at Islamic boarding schools to the surrounding community, especially in the village of Kropoh.